Pendekatan Komunikatif: Mengimplementasikan Metode Langsung dalam Pembelajaran Bahasa Arab - Misni Miratul Hasanah; Dasep Bayu Ahyar; Moh. Yandi Ramdhani (Program Studi Pendidikan Bahasa Arab, 2024)
Learning Arabic is often a challenge for most students, especially non-native speakers. This is caused by several factors, such as differences in language systems, complex grammar, and minimal practice of speaking Arabic in daily life. To overcome this problem, a communicative approach using direct methods can be an effective solution. The direct method focuses on oral communication, where students are encouraged to communicate in Arabic from the start of learning without translating into their mother tongue. This approach emphasizes speaking and listening skills, and introduces vocabulary and grammar naturally through interaction. By practicing direct conversation, students will become familiar with Arabic language patterns and be able to use them spontaneously in meaningful contexts. Applying a communicative approach with direct methods in learning Arabic has several advantages, such as increasing student motivation, developing oral communication skills, and creating a more natural and enjoyable learning atmosphere. However, this approach also requires the active role of teachers in designing learning activities that are interactive and relevant to students' lives.